A general formulation and solution of fuzzy multi-objective linear programming problems - De, P. K.; Chakraborty, A. K.; Deb, Moumita (IEEE International Conference on Computational Intelligence and Computing Research, 2016)
The purpose of this article is to explain how a fuzzy linear programming model can be transformed into a fuzzy multi-objective linear programming model and then solved. An algorithm is developed to present our approach and fuzzy optimal solution is obtained. To demonstrate the efficiency and feasibility of the proposed approach, one numerical example has been solved.